2010
DOI: 10.1097/sla.0b013e3181bfda8c
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning by Hindlimb Occlusion Prevents Liver Ischemic/Reperfusion Injury

Abstract: Brief hindlimb occlusion prevents liver I/R injury. This effect appears to be related to release of HMG-B1 and is dependent on the presence of a functional TLR4. Remote ischemia preconditioning represents a novel approach to preventing distant organ injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 34 publications
3
27
1
2
Order By: Relevance
“…A quantitative comparison of serum transaminases is not possible, as the different models used to study liver IRI, R-IPC, and IPC differ significantly in the amount of liver subjected to ischemia, the length of the ischemic period, the method of preconditioning, and the animal strain [12, 15-19, 30, 33]. Moreover, the results of the R-IPC treatment compared with IRI alone in this model are coherent with earlier R-IPC studies on mice, rabbits, and rats [15][16][17]. When IPC and R-IPC are compared, the results indicate that in this model, R-IPC is less effective than central IPC as only AST levels are significantly affected.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A quantitative comparison of serum transaminases is not possible, as the different models used to study liver IRI, R-IPC, and IPC differ significantly in the amount of liver subjected to ischemia, the length of the ischemic period, the method of preconditioning, and the animal strain [12, 15-19, 30, 33]. Moreover, the results of the R-IPC treatment compared with IRI alone in this model are coherent with earlier R-IPC studies on mice, rabbits, and rats [15][16][17]. When IPC and R-IPC are compared, the results indicate that in this model, R-IPC is less effective than central IPC as only AST levels are significantly affected.…”
Section: Discussionsupporting
confidence: 86%
“…So far it has mostly been studied in cardiac ischemia [14]. Three experimental models have shown lower levels of aminotransferases after liver IRI when then animals were pretreated with R-IPC [15][16][17], although one has failed to do so [18]. In one study on rats, R-IPC was shown to reduce the release of ALT when only the hepatic artery was clamped, but not when the artery as well as the portal vein were clamped [19].…”
Section: Introductionmentioning
confidence: 96%
“…The protective effect of ischemic preconditioning (IPC) in liver ischemia/reperfusion (I/R) injury is well-known [9]. Peralta et al [10] demonstrated that IPC prevents the release of TNF-a from Kupffer cells during the reperfusion phase following hepatic ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…During the reperfusion period, RIPostC was induced by 3 cycles of 5 min of left femoral artery occlusion with a microvascular clamp under an operating microscope, as previously described [26], and 5 min of reperfusion.…”
Section: Methodsmentioning
confidence: 99%